Asuhan Keperawatan pada Pasien Hipertensi dengan Penerapan Terapi Lavender Terhadap Perubahan Tekanan Darah - Nyoman Rudi; Aniska Indah Fari; Veroneka Yosefpa Windahandayani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hypertension, also known as high blood pressure, is an increase in blood pressure, namely a condition where the systolic blood pressure is greater than or equal to 140 mmHg and/or diastolic blood pressure is greater than or equal to 90 mmHg. Lavender aromatherapy is a non-pharmacological therapy that can calm a person. Lavender aromatherapy can increase nitric oxide which is a natural vasodilator, can dilate blood vessels and improve blood circulation so that blood flow becomes smooth and blood pressure decreases. To find out nursing care for hypertensive patients by providing lavender aromatherapy in Sukarami. This case study uses a nursing care process approach carried out on 3 respondents using a case study design. Based on the results of the implementation that has been carried out, there is a change in blood pressure results before and after being given lavender aromatherapy, namely respondent 1's blood pressure was 160/100 mmHg to 146/83 mmHg after being given lavender aromatherapy, respondent 2's blood pressure was 160/90 mmHg to 143/81 mmHg after being given lavender aromatherapy, and respondent 3's blood pressure was 140/90 mmHg to 124/86 mmHg after being given lavender aromatherapy. Of the three respondents, blood pressure decreased after being given lavender aromatherapy for 3 days, the average decrease in systolic blood pressure was 16 mmHg and diastolic blood pressure was 30 mmHg. It is hoped that patients with hypertension can add the application of lavender aromatherapy to non-pharmacological interventions and remain compliant with hypertension treatment and control in health services.